Generalized Distribution of Relaxation Times Analysis for the Characterization of Impedance Spectra - Michael A. Danzer (Batteries, 2019)
Impedance spectroscopy is a universal nondestructive tool for the analysis of the polarization behavior of electrochemical systems in frequency domain. As an extension and enhancement of the standard impedance spectroscopy, the distribution of relaxation times (DRT) analysis was established, where the spectra are transferred from frequency into time domain. The DRT helps to analyze complex impedance spectra by identifying the number of polarization processes involved without prior assumptions and by separating and quantifying their single polarization contributions. The DRT analysis, as introduced in literature, claims to be a model-free approach for the characterization of resistive-capacitive systems. However, a data preprocessing step based on impedance models is often required to exclude non-resistive-capacitive components off the measured impedance spectra. The generalized distribution of relaxation times (GDRT) analysis presented in this work is dedicated to complex superposed impedance spectra that include ohmic, inductive, capacitive, resistive-capacitive, and resistive-inductive effects. The simplified work flow without preprocessing steps leads to a reliable and reproducible DRT analysis that fulfills the assumption of being model-free. The GDRT is applicable for the analysis of electrochemical, electrical, and even for non-electrical systems. Results are shown for a lithium-ion battery, a vanadium redox flow battery, and for a double-layer capacitor.